RESTRICTING DIET AND BULIMIA NERVOSA: A CAUSAL LINK? - Mora Giral, Marisol; Raich Escursell, Rosa María (Anales de Psicología / Annals of Psychology)
We have reviewed available evidence about the relationship between diet and bulimia, mainly all those surveys suggesting a causal link between these variables: longitudinal studies, causal models and experimental evidence. We have examined likewise models, hypothesis and theories providing theorical support for this relationship.